THE AGGRESSIVE JACK TORRANCE IN THE SHINING BY STEPHEN KING: A PSYCHOLOGICAL ANALYSIS - Michael Kevin Bryan Sahertian; Yosep Bambang Margono; Inti Englishtina (LINGUAMEDIA Journal, 2022)
This thesis with a title The Aggressive Jack Torrance in The Shining by Stephen King: A Psychological Analysis. This thesis is a literature study of with the help of psychological theory as a tool to examine the story. Wellek and Warren (1949) opinion about the connection of psychology and literature is the foundation of this thesis. They found out that there is a connection between two of the study, because both of them analyze human being as their subject of study.The theories that writer borrows from psychology discipline are: Abraham Maslow Hierarchy of needs that divide human needs into class. This needs have to be fulfilled in order to function properly as a human being. Second theory in this thesis is called Stress and Coping which explains the definition of stress according to Lazarus and Folkman. The last theory is Frustration-Aggression by John Dollard that describes the aggressive reaction of a frustrated person that cannot attain their goal.The method used in this research is qualitative. Data of this research is from the novel and the film. Several books are used as references to analyze the data and support this research. In collecting data, the writer uses the technique of reading the book and watching the film repeatedly to find out the contents of the story.In this study, the writer learn what happen to Jack Torrance character in The Shining with the aid of Psychological theory. According to Abraham Maslow Hierarchy of needs, a human being has to fulfill his needs in order to function properly. Jack Torrance unable to fulfill his needs in order to function properly as a human being. Besides that, Jack Torrance incapable of acomplish his goals in life, which stress and frustrate him. This frustration, turns into aggression that Jack Torrance take out to the closest people to him, which is his family, Wendy and Danny. Using Stress and Coping, the writer can describe what is stress. This theory function as a tool to analyze Jack Torrance’s stress in the novel. The writer finds out that the source of his stress is because he cannot accomplish his goal. Lastly, using Frustration-Aggression which described Jack Torrance’s aggressive reaction because of his frustration.Another founding of this study is the main problem of Jack Torrance according to conclusion from the analysis of his character in chapter iv. Jack Torrance main source of frustration is his dilemma. He has to choose whether he should be a good husband and father or to be a loyal hotel caretaker. Should he take his son to come down into Sidewinder or should he take care of Overlook Hotel, and keep his family stay at Overlook without medical assistance for his son.